2013
DOI: 10.4304/tpls.3.11.2141-2150
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Field Independence/ Dependence Styles and Reading Comprehension Abilities of EFL Readers

Abstract: Abstract-The present study intends to investigate the relationship between Field Independence/Dependence styles and reading comprehension abilities of intermediate EFL readers as well as to explore their attitude toward reading in a foreign language with respect to their cognitive style. To these aims, ninety university students took part in the study. First, for the purpose of ensuring the homogeneity of the participants they were exposed to Oxford Placement Test (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Ahora bien, varios estudios se han ocupado de explorar la relación entre el estilo cognitivo dic y la lectura. Específicamente, la literatura al respecto ha señalado una fuerte asociación entre dicho estilo cognitivo y la comprensión lectora (Sabet y Mohammadi, 2013), teniendo en cuenta la velocidad y la ejecución de microprocesos lectores tales como la decodificación, el análisis sintáctico (Kirchner, 1987) y el análisis semántico (Camargo-Uribe y Hederich-Martínez, 2004). En esta dirección, las investigaciones han reportado que los sujetos independientes de campo obtienen mejores resultados en pruebas de lectura (Hederich-Martínez y Camargo-Uribe, 2016; Suh, 2009), especialmente cuando dichas pruebas demandan habilidades analíticas (Salmani-Nodousham, 2007), recuperación de información, uso de pistas contextuales y prueba de hipótesis (Sabet y Mohammadi, 2013).…”
Section: Estilo Cognitivounclassified
“…Ahora bien, varios estudios se han ocupado de explorar la relación entre el estilo cognitivo dic y la lectura. Específicamente, la literatura al respecto ha señalado una fuerte asociación entre dicho estilo cognitivo y la comprensión lectora (Sabet y Mohammadi, 2013), teniendo en cuenta la velocidad y la ejecución de microprocesos lectores tales como la decodificación, el análisis sintáctico (Kirchner, 1987) y el análisis semántico (Camargo-Uribe y Hederich-Martínez, 2004). En esta dirección, las investigaciones han reportado que los sujetos independientes de campo obtienen mejores resultados en pruebas de lectura (Hederich-Martínez y Camargo-Uribe, 2016; Suh, 2009), especialmente cuando dichas pruebas demandan habilidades analíticas (Salmani-Nodousham, 2007), recuperación de información, uso de pistas contextuales y prueba de hipótesis (Sabet y Mohammadi, 2013).…”
Section: Estilo Cognitivounclassified
“…Sabet & Mohammadi studied the relationship between the same cognitive style and reading comprehension abilities of EFL learners, resulting in a significant difference between FD and FI learners. [14] Ali & Hasan conducted a study among 305 students to determine the relationship among FD-FI cognitive style, English reading and academic success. Results showed that the cognitive style correlates with reading comprehension score, English language learning and academic achievement with coefficient of determination of 8.8%, 9.2% and 11 .6% respectively.…”
Section: Studies On the Relationship Between Fd-fi Cognitive Style And English Reading Comprehensionmentioning
confidence: 99%